Japan : - Lincoln, Edward J. (Brookings Institution, 1988)
Contents: Japan is the great economic success story of the postwar period, growing at unprecedented rates to become one of the world's most advanced industrial nations. But since the early 1970s, Asia's economic giant has had to contend with many of the problems encountered by Western economies--slower growth, increased unemployment, rapid changes in the financial and industrial sectors--problems that have permanently transformed its economy and pose crucial challenges for its leaders.